New Findings on Al-Insaf According to the Al-Mobahesat of Avicenna - Hosein Kalbasi Ashtari; Mohammad Hossein Ansari; Mohammad Broomand (حکمت سینوی)
In order to comprehensively describe and explain the intellectual system of Sheikh Al-Raees Abu Ali Sina, especially to recognize the amount and quality of his philosophical innovations, it is necessary to refer and cite his lesser-known works, including the book Al-Insāf. This necessity goes back not only to the need to complete the geometry of his "Eastern wisdom", but also to the correct presentation of the principles and foundations of the philosophical thought of the Islamic world and the degree of independence and identity of the phenomenon called "Islamic philosophy". Another aspect of the importance of this reference and research is that Ibn Sina, in the mentioned book, examines and evaluates the opinions of the old and new commentators of Aristotle, among the conventional philosophical traditions up to his time. Something that can be seen in few works of this kind. Despite the certainty of attributing the authorship of the work to Ibn Sina, there are many questions about the themes and subjects of this book. In addition, discussions have been raised about the time of creation and authorship of the work, the quantity and quality of the content, and the issue of its rewriting. In this article, an attempt has been made to answer some of the aforementioned questions by using historical and philosophical sources and parts of the text of the Al-Mubahasat as an important witness and proof. In general, it should be said that Al-Insāf has an original version and a rewritten version, and in each of them, Ibn Sina had a different treatment compared to the descriptions of Aristotle's books. His effort has been to resolve the ambiguities in Aristotle's books based on rational and definite criteria, while making a fair judgment between different opinions, by determining the principles that he obtained from the main books of wisdom. In the meantime, the process of Avicenna's and his students' scientific relations with the thinkers of that time, especially the people of Baghdad, has been clarified to some extent. In order to refer to Ibn Sina's own works and literature in this context, the translation of a part of the text and the appendices of Al-Mubahasat have been attached to this article.